Development of Learning E-Modules Based on Contextual Teaching and Learning on the Material of Changing the Form of Energy to Improve Students' Science Literacy - Alamin Alamin; Nurhanurawati Nurhanurawati; Fatkhur Rohman; Ryzal Perdana (Postgraduate, University of Mataram, 2024)
The low science literacy of students is caused by the lack of utilization of technology in learning activities such as the use of teaching materials. One way to improve students' science literacy is to develop innovative learning materials such as learning e-modules. This study aims to produce contextual teaching and learning-based learning e-modules on IPAS Phase B learning, material for changing the form of energy to improve the science literacy of students in elementary school. This research is a type of Research and Development (R&D) research, the development was carried out referring to the Borg & Gall theory. Data collection tools use valid and reliable test instruments. Based on the results of the material, media and language expert validation test of the validity of the contextual teaching and learning-based learning e-module product obtained an average value of 0.813 with decent criteria. Furthermore, the results of the educator's response test to the contextual teaching and learning-based learning e-module users obtained 86.88 with very practical criteria, while the response of students obtained an average value of 97.59 with very practical criteria. Then the results of the data effectiveness test using the paired t-test with the calculation result of 0.000 < 005 means that there is a significant difference between before being given treatment with contextual teaching and learning-based learning e-modules and after being given the treatment. Based on the data obtained from the results of the study, it can be concluded that the contextual teaching and learning-based learning e-module on the material of changing the form of energy is valid, practical, and effective to improve the science literacy of students in elementary schools